2013
DOI: 10.1097/pas.0b013e31827332b0
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathologic Analysis of Combined Hepatocellular-Cholangiocarcinoma According to the Latest WHO Classification

Abstract: Combined hepatocellular-cholangiocarcinoma comprises <1% of all liver carcinomas. The histogenesis of combined hepatocellular-cholangiocarcinoma has remained unclear for many years. However, recent advances in hepatic progenitor cell (HPC) investigations have provided new insights. The concept that combined hepatocellular-cholangiocarcinoma originates from HPCs is adopted in the chapter "combined hepatocellular-cholangiocarcinoma" of the latest World Health Organization (WHO) classification. In this study, we … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
134
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 137 publications
(144 citation statements)
references
References 42 publications
10
134
0
Order By: Relevance
“…24). In addition, the existence of mixed hepatocellular cholangiocarcinoma (HCC-iCCA) tumors (25), a subtype with predominance of stem cell features, points out the presence of a possible common cell of origin. Thus, iCCA is currently believed to derive from biliary epithelial cells (cholangiocytes) of the intrahepatic biliary tract, hepatic progenitor cells (HPC), or even mature hepatocytes.…”
Section: Cells Of Originmentioning
confidence: 99%
“…24). In addition, the existence of mixed hepatocellular cholangiocarcinoma (HCC-iCCA) tumors (25), a subtype with predominance of stem cell features, points out the presence of a possible common cell of origin. Thus, iCCA is currently believed to derive from biliary epithelial cells (cholangiocytes) of the intrahepatic biliary tract, hepatic progenitor cells (HPC), or even mature hepatocytes.…”
Section: Cells Of Originmentioning
confidence: 99%
“…Therefore, it is thought to be difficult to diagnose CoCC preoperatively. Furthermore, there are reports that CoCC is composed of three different areas histologically-CoCC, hepatocellular carcinoma-like, and CCC-like 3,20 -which supported the hypothesis that CoCC is derived from hepatic stem cells. However, because of the heterogeneous distribution of cells in CoCC, needle biopsy may yield different results depending on the region of the tumor that is biopsied.…”
Section: Discussionmentioning
confidence: 51%
“…HPCs also express cholangiocytes markers (CK19) moderately and HSCs marker (CD45 and CD109) strongly. Akiba et al (2013) CD56, c-kit (CD117), CD133, EpCAM Badrawy et al (2013) OV6, AFP Chen et al (2015) OV6, CK19 Hao et al (2013) EpCAM, CD133, AFP, EFNA1 Jia et al (2013) OV6 Li et al (2014) Alb, AFP, CK8, CK18, CK19, CD90, c-kit (CD117), OV6, CD45, CD109 Libbrecht et al (2000) CK7, CK19, CK8, CK18, Chrom-A, OV6 Petersen et al (1998) AFP, GGT, OV6, CK19, OC2, Thy-1 Van Den Heuvel et al (2001) OV6, CK19 Ye et al (2014) EpCAM, OV6, CD133, c-kit (CD117) Yun et al (2013) CK19, Oct-3/4, EpCAM, DLK1 Yovchev et al (2007) EpCAM, CD44, CD24, CD133 In addition, Ye et al (2014) used four markers for HPCs (EpCAM, OV6, CD133 and c-kit) and found that HPCs express HSCs marker (c-kit and CD133) and express biliary marker (EpCAM). Another HSCs marker used to identify HPCs was Thy-1 (Petersen et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Another marker that is also possible to be used as oval cells' marker is CD56. The expressions of CD56 indicate regenerative condition of liver cells and were found in ductular cells and oval cells (Van Den Heuvel et al, 2001;Akiba et al, 2013)). OC2 is the other traditional marker that can be used for oval cells.…”
Section: Discussionmentioning
confidence: 99%